60 GHz low‐power LNA with high gm × Rout transconductor stages in 65 nm CMOS. Issue 4 (1st February 2017) - Li, Zhiqun; Wang, Chong; Li, Qin; Wang, Zhigong
Abstract : This Letter presents a 60 GHz low power low noise amplifier (LNA) with high g m × R out transconductor stages in a 65‐nm complementary metal oxide semiconductor (CMOS) technology. Different from the cascode and current‐reused common source–common source (CS–CS) structure, the new transconductor proposed in this Letter comprises a CS transistor whose DC current is shared by other two transistors. With this configuration, the equivalent transconductance, g m and output resistance, R out of the transconductor are both high while its noise figure is deteriorated slightly comparing with CS structure, making it suitable for low‐power LNA circuits. From the measurement results, the LNA gets a gain of 13.4 ± 1.5 dB and 3‐dB bandwidth of 16.7 GHz (48–64.7 GHz). The average noise figure of the LNA is 6.1 dB with a power dissipation of 9.6 mW under 1 V power supply.